Analisis Penggunaan Bahasa Daerah dalam Pembelajaran Pada Anak Usia 5-6 di TK Dharma Wanita Labuhan Haji Barat - Nurwanti, Khairiatul; Lina Amelia (Institut Agama Islam Negeri Madura, 2024)
The use of regional languages ​​in learning is part of the independent curriculum. This research aims to analyze the intensity, advantages and weaknesses of the use of regional languages ​​in learning at the Dharma Wanita Labuhan Haji Barat Kindergarten. The research method used is descriptive qualitative. The sampling technique used was purposive sampling, namely 31 children and 2 teachers with the aim of classes using regional languages. Data was collected through direct observation and structured interviews with teachers at the kindergarten. The results of the research show that the intensity of using regional languages ​​in learning is often used in class B. The advantage of using regional languages ​​in learning is that children easily understand the material. The weakness of using regional languages ​​in learning is that a small number of children who cannot use regional languages ​​are unable to understand the material presented by the teacher. This means that regional languages ​​are effectively used in learning because the majority of children understand regional languages ​​as an introductory language in learning. So, it can be understood that the use of regional languages ​​has a positive impact on children's understanding and involvement in learning, as well as strengthening their cultural identity